Upaya Peningkatan Motivasi Belajar pada Perkuliahan Offline dan Online - Setiawan, Soni; Khalid, Abdullah (Journal of Comprehensive Science, 2024)
This research is based on the anxiety of students of the Islamic education guidance and counseling study program at Pelita Bangsa University regarding lectures conducted online and also anxiety about lectures conducted offline. From these two problems, it was found that students who undergo online lectures are anxious because of boring, sleepy, unfocused learning because of distraction from others and wasteful internet packages and network constraints. This makes learning in online lectures less effective. But on the other hand, lectures that are carried out offline are still felt to be lacking because students who experience long distances have difficulty coming to campus, are used to being online so they are lazy to go to campus, and take up time because of a lot of work at home. The author took steps to solve the problem by going through the middle path (At-Tawasuth), which is not leaning to the right and not leaning to the left, so steps were taken to increase learning motivation in offline and online lectures. The efforts made by Universitas Pelita Bangsa in taking the middle way are a combination of online and offline lectures with the method of one week offline and one week online. This is to provide justice for students who want online lectures, as well as for students who want offline lectures.